2021
DOI: 10.1021/acs.energyfuels.1c00197
|View full text |Cite
|
Sign up to set email alerts
|

Subsurface Microbial Invasion Affects the Microbial Community of Coal Seams

Abstract: Coal seam microorganisms have attracted much attention for their special functions that are closely related to secondary biogenic gas formation, but the influence of subsurface microbial invasion on coal microorganisms remains poorly understood. In this study, subsurface microorganisms from soils at different depths were used to infect coal samples, and the abundance and composition of the microbial community were analyzed by quantitative polymerase chain reaction (PCR) and high-throughput sequencing. The resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…Coal seams are important underground anaerobic habitats in the world. The main methanogenic archaea in such anaerobic habitats differ greatly due to the difference of coal forming age (Liu et al, 2019), pre coal material (Wang et al, 2018), sedimentary environment (Tanikawa et al, 2018) and microbial sources (Vick et al, 2019b;Li et al, 2021). Methanosarcina were dominant archaea in the pristine Pniówek coal due to their metabolic flexibility (Pytlak et al, 2020).…”
Section: Binning Results and Identificationmentioning
confidence: 99%
“…Coal seams are important underground anaerobic habitats in the world. The main methanogenic archaea in such anaerobic habitats differ greatly due to the difference of coal forming age (Liu et al, 2019), pre coal material (Wang et al, 2018), sedimentary environment (Tanikawa et al, 2018) and microbial sources (Vick et al, 2019b;Li et al, 2021). Methanosarcina were dominant archaea in the pristine Pniówek coal due to their metabolic flexibility (Pytlak et al, 2020).…”
Section: Binning Results and Identificationmentioning
confidence: 99%
“…Metagenomic analyses revealed that both endophytic and epiphytic microorganisms are abundant in the LRC environment, as coal is generally originated from plant materials and therefore exhibits inherent plant interaction abilities [88][89][90]. LRC supplementation usually promotes the relative abundance of Actinobacteria.…”
Section: Effects Of Lrc On Soil Microbial and Biochemical Qualitiesmentioning
confidence: 99%